Solving Leontief's Paradox with endogenous growth theory - George Sorg-Langhans; Clemens Struck; Adnan Velic (University College Dublin, UCD School of Economics, 2018)
Theories of international trade have severe difficulties in explaining why, despite i) substantial differences in factor-proportions across industries and ii) considerable cross-country differences in capital-labor ratios, the iii) the evidence for factor-proportions trade is rather weak. We propose a simple explanation of this well known finding: standard trade theories treat important forces such as the distribution of productivity within the economy as exogenous. We argue instead that the productivity allocation is endogenous and counter-balances factor-proportion differentials be- tween countries. Consequently, comparative advantage across countries of different development levels is negligible and this is why the incentives for trade are low.
Keywords: F11; F14; F41; O47; 330; factor-proportions trade; Heckscher-Ohlin-Vanek; macroeconomic general equilibrium mo- dels; endogenous growth; biased productivity